Caracterización del polen de especies de los géneros Passiflora y Dilkea - Barrios Arango, L; Caetano, C.M.; Cardozo Conde, Carlos Iván; Coppens d'Eeckenbrugge, Geo; Arroyave, José A.; Olaya, Cristian A. (2005)
Pollen characterization of genera Passiflora and Dilkea. 156 accessions of 121 species of Passiflora and two species of Dilkea were collected in the field or gathered from national herbaria. The samples were analyzed by using optical and scanning electron microscopy D. margaritae has a pollen of medium size, but in an inferior range, prolate to subprolate, and tricolporate, while D. acuminata has a pollen of medium size, oblate-spherical, 4-partially 5-colporate. The pollen of both species is reticular, and the lumina have more irregular diameter in D. margaritae. In Passiflora, the pollen is medium, but with a wide variation (small to large), prolate to oblate-spherical, reticulated, with lumina of irregular diameter, except for P. macrophylla and P. sp (subgenus Astrophea), whose reticulum is constituted by residual muri.